Faktor-Faktor yang Mempengaruhi Kemiskinan di 9 (Sembilan) Kota di Provinsi Jawa Timur - Yustie, Renta (OECONOMICUS Journal of Economics, 2020)
This research aims to analyze effect from human development index (HDI), dependency ratio, open unemployment rate to poverty is partially and simultaneously. Data used in research is secondary data are poverty, human development index (HDI), dependency ratio, open unemployment rate overall in percentage (%)., with used analyze of multiple linier regression methode. This result is human development index (HDI), dependency ratio, open unemployment rate have a effect to partially and simultaneously to poverty.